Somatic aspects of suffering Progress in relieving pain, dyspnoea and other cancer symptoms - Kotlińska-Lemieszek, Aleksandra; Bączyk, Ewa; Łuczak, Jacek (Contemporary Oncology/Współczesna Onkologia, 2000)
Progressive damage of body caused by chronic life-threatening disease, serious side effects of therapy (common in anticancer treatment) and by other concurrent illness (cancer most frequently occurs in patients over 65 years) are the sources of multidimensional suffering of terminally ill patients and the suffering of their beloved Suffering as a whole person experience should be considered in all aspects of humane life including bodily (somatic), psycho-social and spiritual (existential) dimensions. All the above mentioned factors influence each other and have an important impact on the dynamics and intensity of total pain (suffering). The somatic component consist of occurrence of several distressing symptoms adding to unfavourable body image and disability. The detailed clinical assessment and recognition of the causes of various symptoms, play an important role in developing a plan of successful symptoms management and improvement of the patient’s quality of life. The achievements in palliative medicine include improvement in knowledge and skill of monitored pharmacotherapy allowing to control the pain, dyspnoea and other symptoms effectively.